IMPROVEMENT AND RESEARCH OF WELLBORE PACKER SEAL - Rachkevych, R. V.; Shkitsa, L. Ye.; Faflei, I. Ya.; Matvienkiv , O. M.; Myndiuk , V. D.; Kovtun , V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The article describes the problem of increasing the tightness of the seals of well packers, which are important elements of operational and technological equipment of oil and gas wells. Packers isolate separate well intervals, which is necessary to perform technological operations, such as hydraulic fracturing of a productive horizon, injection of water or gas to maintain productive horizon pressure, carry out thermal and acid treatments and tests of casing and mouth equipment. The effectiveness of these processes, the safety of staff and the prevention of accidents in the well depends on the tightness of the packer. The article analyzes the design of the packers sealing units and the factors that affect their work. It is shown that the main problem when using traditional smooth rubber cuffs is the uneven distribution of contact stresses along the surface of the seal. This is the cause of intense wear of rubber, reducing tightness and increasing the risk of breakthrough of the working environment. It is established that seals materials should meet the requirements for resistance against aggressive environment, high temperatures and pressures, as well as deformation. To study the functioning of the sealing unit, simulation modeling was made by the method of finite elements using a model of Muni -Rivlin, which adequately describes the nonlinear behavior of rubber materials. The model allowed to determine the distribution of contact pressure between the cuff and the casing, as well as to evaluate the effect of the geometry of the seal, the friction coefficient and the installation efforts on the tightness of the system. On the basis of modeling results, an advanced structure of the sealing element with a corrugated surface was developed, which provides a more uniform distribution of stresses and increase contact pressure in contact areas. Our research have shown that the use of a corrugated cuff allows to increase the sealing capacity by 15-20% with the same or smaller installation efforts regarding to a standard smooth seal. It is also established that the increase of the friction coefficient between the rubber and the metal surface causes partial unloading of the upper seal, which can cause loss of tightness. To reduce this effect, it is recommended to use special lubricants and surface coatings that provide stable friction and improve the fit of the cuffs to the casing. The results of the article have of great practical importance for improving the new generation well packers.